STRENGTHENING DEMOCRACY: THE ROLE OF ELECTORAL JUSTICE AND THE ELECTION SUPERVISORY BOARD IN ENSURING FREE AND FAIR ELECTIONS IN INDONESIA - Harahap, Ali Umar (Jurnal Hukum Progresif, 2025)
The general election is an essential manifestation of constitutional democracy practised in many countries, including Indonesia. Democracy, originating from the Greek term “rule by the people,” is understood in modern thought as a representative system in which representatives are chosen through free, competitive elections. A democratic election must adhere to universally accepted principles, such as being direct, universal, free, secret, honest, and fair. The electoral justice system, a key instrument of the rule of law, ensures the proper enforcement of these principles by resolving disputes fairly and promptly. Its design is integral to the legitimacy and credibility of elections, reflecting the socio-cultural and political context in which it operates. The system must be guided by values and norms, ensuring the independence and impartiality of election administration, transparency, accessibility, inclusivity, and the right to an effective remedy for violations. Election law enforcement is crucial for maintaining the credibility of elections, providing legal certainty, and fostering trust in the election process. This research explores the Election Supervisory Board’s role in resolving electoral disputes through quasi-judicial mechanisms. It examines the legal framework for resolving election-related disputes, emphasising the importance of an effective electoral justice system in maintaining free and fair elections. The research method involves doctrinal legal analysis, focusing on laws and regulations, particularly Law No. 7 of 2017 on General Elections. By examining adjudication processes and administrative efforts in electoral disputes, the study highlights the evolving role of the Election Supervisory Board in strengthening Indonesia's democratic processes. It concludes that a well-designed electoral justice system is fundamental to ensuring democratic integrity and public trust in election outcomes.